Clinicopathological description of testicular seminoma with liver metastasis in a Saint-Bernard dog - Gati de Souza, G. [UNESP] (2024)
A twelve-year-old male Saint-Bernard dog weighing 46.0 kg was referred to the pathology laboratory at the veterinary hospital for an autopsy. The patient had a history of apathy, hyporexia, polydipsia, increased rectal temperature, decreased body condition score, muffled cardiac auscultation, hypoglycemia and hepatomegaly. The dog developed cardiorespiratory arrest on the same day and was subsequently referred for post-mortem examination. In the necropsy, the macroscopic evaluation hepatopathy with the liver in the aspect of “nutmeg”, scrotal sac with abrasions, and the presence of a nodular lesion in the testes. Histopathology confirmed a diagnosis of testicular seminoma with liver metastasis. Testes are the third most common localization for dog tumors. However, metastasis of seminoma is uncommon. Thus, the case brings clinicopathological description of a rare case of testicular seminoma with liver metastasis in a Saint-Bernard.